1999
DOI: 10.1046/j.1460-9568.1999.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, immunophenotypical and electrophysiological properties of resting microglia in vitro

Abstract: Morphological, immunophenotypical and electrophysiological properties were investigated in isolated cultured murine microglia before and after exposure to astrocyte-conditioned medium (ACM). Following application of ACM, microglial cells underwent a dramatic shape transformation from an amoeboid appearance to a ramified morphology. In parallel to morphological changes, a downregulation of macrophage surface antigens was observed in microglia exposed to ACM. Staining intensities for major histocompatibility com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 45 publications
3
45
0
Order By: Relevance
“…We first compared calcium signals to C5a application in microglial cells of standard cultures and in microglial cells with ramified morphology that were cultivated in two different conditioned media and resembled the 'resting' microglia in vivo (Eder et al 1999;Kloss et al 2001). Under all three culture conditions, most of the cells responded with marked calcium signals irrespective of their morphological appearance (Figs 2c-e).…”
Section: Discussionmentioning
confidence: 99%
“…We first compared calcium signals to C5a application in microglial cells of standard cultures and in microglial cells with ramified morphology that were cultivated in two different conditioned media and resembled the 'resting' microglia in vivo (Eder et al 1999;Kloss et al 2001). Under all three culture conditions, most of the cells responded with marked calcium signals irrespective of their morphological appearance (Figs 2c-e).…”
Section: Discussionmentioning
confidence: 99%
“…For electrophysiology, microglia were plated on 15-mm sterile glass coverslips and cultured in either serum-free medium (i.e. MEM with 2% B27 supplement (Invitrogen), 2 mM L-glutamine, and 0.05 mg/ml gentamycin) or astrocyte-conditioned medium (ACM), collected as the supernatant from rat astrocyte cultures grown in MEM with 2% fetal bovine serum (21). ACM was collected twice a week, frozen at Ϫ70°C, and used within one month.…”
Section: Methodsmentioning
confidence: 99%
“…An Outward-rectifying Cation Current-Unless otherwise indicated, all recordings were from microglia that were cultured in serum-free medium or astrocyte-conditioned medium, conditions that reduce microglia activation (21). We patch-clamped microglia that were unipolar or bipolar with elongated cell bodies, as in one of our earlier studies (12).…”
Section: Biophysical Properties Of the Trpm7-like Current In Rat Micrmentioning
confidence: 99%
“…Several studies showed that astrocytes play a significant role in the differentiation and transformation. Ameboid microglial cells have been shown to ramify when they are cultured on monolayers of astrocyte (Liu et al, 1994;Sievers et al, 1994;Tanaka and Maeda, 1996) or treated in vitro with astrocyteconditioned medium (Eder et al, 1999;Suzumura et al, 1990). Astrocyte-derived granulocyte/macrophage-colony stimulating factor and macrophage colony stimulating factor can induce microglial ramification in vitro (Ohsawa et al, 1997;Schilling et al, 2001;Suzumura et al, 1990), and astrocytes release serine and glycine into the culture medium and both amino acids enhance ramification of microglial cell (Tanaka et al, 1998).…”
Section: Introductionmentioning
confidence: 99%